ENHANCING WOMEN’S LEADERSHIP IN BUSINESS THROUGH GENDER-INCLUSIVE STRATEGIES AND WORK-LIFE SUPPORT - IBRAHIM, KADIRI KAYODE; OMOWUNMI, ADENIREGUN AWAWU; OKORONKWO, PATIENCE NNENNA; OWONIYA, KEMISOLA IWALOLA (JOURNAL OF ECONOMICS AND ALLIED RESEARCH, 2025)
This article examines the strategic influence of gender diversity initiatives and work-life balance policies on the advancement and sustainability of women’s leadership in business administration. Drawing from a mixed-methods approach involving survey responses from 106 women and interviews with five female executives, the study analyses how inclusive organisational structures either facilitate or hinder leadership progression for women. Quantitative data revealed that 74% of respondents credited gender diversity policies with supporting their rise to leadership, while 81% highlighted work-life balance as a key factor in retaining their positions. Using Herzberg’s Two-Factor Theory and Organisational Behavior Theory as analytical frameworks, the study found that the absence of supportive work conditions and inclusive culture significantly reduces women’s career satisfaction and progression. The article concludes that gender diversity and flexible work practices are not only ethical imperatives but also strategic enablers for sustainable leadership. It recommends institutional reforms that embed gender parity targets, normalise flexible work arrangements, and promote inclusive leadership development pipelines. These findings contribute to the discourse on structural gender equity and offer actionable insights for policymakers and organisational leaders in developing contexts, particularly Nigeria.